2017
DOI: 10.1194/jlr.m068197
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol acyltransferase 2 links glucose utilization to fatty acid oxidation in the brown adipocytes

Abstract: Brown adipose tissue uptake of glucose and fatty acids is very high during nonshivering thermogenesis. Adrenergic stimulation markedly increases glucose uptake, de novo lipogenesis, and FA oxidation simultaneously. The mechanism that enables this concerted response has hitherto been unknown. Here, we find that in primary brown adipocytes and brown adipocyte-derived cell line (IMBAT-1), acute inhibition and longer-term knockdown of DGAT2 links the increased de novo synthesis of fatty acids from glucose to a poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 70 publications
4
52
1
Order By: Relevance
“…P values were obtained from unpaired 2-tailed t tests. free fatty acids are then either rapidly oxidized or activate UCP1 in mitochondria (14). Our findings of similar b3 adrenergic receptor-stimulated 18 F-FDG/2-deoxy-3 H-glucose uptake between WT and UCP1 KO brown adipocytes suggest that UCP1 (thermogenic) function does not provide feedback, on the initial step at least, of this concerted process.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…P values were obtained from unpaired 2-tailed t tests. free fatty acids are then either rapidly oxidized or activate UCP1 in mitochondria (14). Our findings of similar b3 adrenergic receptor-stimulated 18 F-FDG/2-deoxy-3 H-glucose uptake between WT and UCP1 KO brown adipocytes suggest that UCP1 (thermogenic) function does not provide feedback, on the initial step at least, of this concerted process.…”
Section: Discussionmentioning
confidence: 71%
“…In mouse primary brown adipocytes treated with CL 316,243, glucose is transported into the cell and through the action of diacylglycerol acyltransferase 2 feeds into specialized lipid droplet pools, which are simultaneously hydrolyzed (14). The released Values are mean ± SEM.…”
Section: Discussionmentioning
confidence: 99%
“…The above‐mentioned study by Irshad et al revealed that lipolysis is required for the full oxidation of glucose in brown adipocytes but did not address its role in UCP1‐mediated thermogenesis. Initial pharmacological experiments performed on cultured differentiated mouse brown and brite/beige adipocytes with ATGL and hormone‐sensitive lipase (HSL) inhibitors suggested that lipolysis is mandatory for thermogenesis .…”
Section: The Importance Of Lipolysis For Bat Thermogenesismentioning
confidence: 99%
“…S-2). Based on these results and available literature 11,16,36 , concentrations for further experiments were determined to be 1 µM (D1i) and 10 µM (D2i). Furthermore, visual observation and measurement of cell protein content indicated none cell-toxic effects with neither D1i (1 µM) nor D2i (10 µM) up to 24 h treatment.…”
Section: Effect Of Dgat Inhibitors On Distribution Of Exogenous Oa Inmentioning
confidence: 99%
“…For instance, the enzymes demonstrated to have non-redundant roles in intestinal lipid metabolism in mice enterocytes 14 . In liver and brown adipose tissue, DGAT1 seems to favour the incorporation of exogenous supplied FAs, whereas DGAT2 appears to be an enzyme of major importance for TAG synthesis of FAs derived from de novo lipogenesis 11,15,16 . Moreover, DGAT1 and DGAT2 have recently been shown to have distinct and overlapping functions for TAG synthesis in adipocytes 17 , where DGAT1 have been linked to the lipolysis-re-esterification cycle of preformed FA, a process that may also protect the endoplasmic reticulum from lipotoxic stress and adipose tissue inflammation 18 .…”
mentioning
confidence: 99%